Pendanaan Pendidikan Di Indonesia - Syakdiah, Syakdiah (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2005)
Education is universal basic human need. The Indonesian state founder also realize that matter Hence